Development of Inorganic Carrier Based Bioformulation of Sebacina Vermifera and Its Evaluation on Trigonella Foenumgraecum (Funded work) - Kamal Jeet; Ashish Baldi (International Journal of Pharma and Bio Sciences, 2020)
Deleterious effects of chemical fertilizers have raised concern to find alternate methods of production in sustainable manner. Bio fertilizers, composed of bio inoculants are promising alternate and widely in prevalence to achieve sustainable, cost-effective and eco-friendly agriculture outcomes. Applications of such bio fertilizers have been proved beneficial to economic, ornamental and medicinal plants in aspects of phyto promotion, yield enhancements, and secondary metabolite productions. The present study focuses on the development of inorganic carrier-based bio formulation, comprising bio-inoculant (Sebacina vermifera) and to optimize best carrier material among clay, vermiculite and talcum powder with respect to viability and performance. The viability of formulations was evaluated at an interval of 30 days for one year. The performance of formulations was evaluated on the growth of Trigonella foenumgraecum under greenhouse and field conditions. Growth evaluation was done periodically after an interval of 30 days i.e. 30, 60, 90 and 120 days after transplantation and plants were evaluated for shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight and root dry weight. It is observed that talcum powder retains the highest viable count and talcum based bio formulation containing S. vermifera is best among all inorganic carrier-based bio formulations and supported by shelf life study and the magnitude of growth promotions under both pot and field conditions. Talcum powder has all the potential to be the best carrier for the efficient delivery of fungal propagules. Talcum based bio formulation containing propagules of Sebacina vermifera, proved significant to alter the growth of Trigonella foenumgraecum therefore the formulation could be prove a novel alternate to enhance the production of crops, medicinal and aromatic plants in a safe and long term beneficial perspectives.